Akronim dalam Bahasa Arab - Abu Sufyan (Humaniora, 2011)
Abreviation is a morphemic process. In Arabic one of the abreviation processes is annaht. This process plays a significant role in the development of Arabic in general, and its vocabulary in particular.The result shows that structurally annaht in Arabic derives from combining two or more elements into one word; this process occurs either by eliminating a fart of the elements of the consonanst or combining all of the elements, written/pronounced as one syllable/phonem. Annaht can be formed frm words, phrases and sentences. Semantically, the meanings of the determining elements forming annaht and those of the annaht itself have either direct or indirect relationship. The meaning of annaht can be synonymous with, more specific, more general than or associated with that of the determining elements.